Inheritance of spike color in einkorn wheat (Triticum monococcum L.) - Hao Fu (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія, 2022)
Aim: specify the spike color inheritance in einkorn wheat (Triticum monococcum L.) hybrids. Methods: reciprocal hybrids between the black-spikeed UA0300282 and white-spikeed UA0300311 cultivated einkorn accessions were created with the use of the “single cross” method. Four generations were analyzed using the segregation analysis method: P1, P2, F1, and F2 at autumn and spring sowing. Results: it was found that for the combination UA0300311 × UA0300282 at autumn sowing, the most suitable inheritance model is MX2-EA-AD, which implies the presence of two main genes with an equal additive effect plus polygene systems with an additive-dominant effect. In the plants of spring sowing, spike color is described by the MX2-CD-AD model, which suggests the presence of two major genes with full dominant effect plus polygenes with additive-dominant effect. In the reciprocal combination UA0300282 × UA0300311, the optimal model that describes best the spike color dispersion in plants of autumn sowing is MX2-ADI-AD, which suggests the presence of two main genes with an additive-dominant-epistatic effect plus polygenes with the additive-dominant effect. Distribution of the spring-sowing plants in terms of the spike color is well described by the MX2-ADI-ADI model – two main genes with an additive-dominant-epistatic effect plus a system of polygenes also with an additive-dominant-epistatic effect. The genes manifest themselves differently in the trait control depending on the weather conditions determined by the sowing time. In the group of direct combination plants (UA0300311 × UA0300282) of autumn sowing, heritability determined by the main gene is 97%, while that determined by polygenes is 2.7%; at spring sowing, these values are 67% and 32% respectively. In the reciprocal combination (UA0300282 × UA0300311) of autumn sowing, the main genes heritability effect is 99%, and the polygenic system accounts for 1%; in plants of spring sowing, respectively, 72%, and 28%. Conclusions: on the basis of the spike color expressiveness in the crossing combination of the einkorn kinds of wheat UA0300311 × UA0300282, the parental forms differ in two main genes and polygenes. The ratio of spike color heritability components depends on the growing conditions: at autumn sowing, 97–99 % of heritability is determined by the main genes, the polygenes account for 1–3 % of phenotypic variability; at spring sowing, the heritability component increases to 28–33 % due to the polygenic complex.